Provable Security 9th International Conference, ProvSec 2015, Kanazawa, Japan, November 24-26, 2015, Proceedings - Au, Man-Ho.; Miyaji, Atsuko; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 9th International Conference on Provable Security, ProvSec 2015, held in Kanazawa, Japan, in November 2015. The 19 full papers and 7 short papers presented together with 3 invited talks were carefully reviewed and selected from 60 submissions. The papers are grouped in topical sections on fundamental, protocol, authenticated encryption and key exchange, encryption and identification, privacy and cloud, leakage-resilient cryptography and lattice cryptography, signature and broadcast encryption.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Application software; Computers and civilization; Management information systems; Computer Science; Data Encryption; Systems and Data Security; Computers and Society; Computer Appl. in Administrative Data Processing; Management of Computing and Information Systems; Electronic books